-4(3-P)=p-3

Simple and best practice solution for -4(3-P)=p-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3-P)=p-3 equation:


Simplifying
-4(3 + -1P) = p + -3
(3 * -4 + -1P * -4) = p + -3
(-12 + 4P) = p + -3

Reorder the terms:
-12 + 4P = -3 + p

Solving
-12 + 4P = -3 + p

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 4P = -3 + 12 + p

Combine like terms: -12 + 12 = 0
0 + 4P = -3 + 12 + p
4P = -3 + 12 + p

Combine like terms: -3 + 12 = 9
4P = 9 + p

Divide each side by '4'.
P = 2.25 + 0.25p

Simplifying
P = 2.25 + 0.25p

See similar equations:

| 8x+5+5x-6=90 | | 30(1/3m-3/5n)-20(3/4m+2/5n) | | 3x-4+7-x=13-4x+2+x | | y=-2*1+5 | | 42/3x9 | | (1-(-x)^2)/-1 | | y=-2*-2+5 | | 9x42/3 | | y=-2x^3-9x^2-10x-3 | | y/2+1=3/2 | | 6x+2(x-10)= | | -u-3=12 | | 0.4t=0.5+0.6t | | -51+8=n | | 4/5-678*7 | | 3x^2+24x-7=0 | | 0.2(8-6h)=h | | 14x^2-11xy-15y^2=0 | | 3x+47=180 | | 12.25-.75=x | | 4+(a/5)=2 | | 1+6=3+2x | | -3(3y-4)-y=-2(y-4) | | 1-9/6x=2/5 | | 1+3y=5/3y | | (3x-1)/4=-5/11 | | 2/3(6y+9)=20 | | 4(x-1)-2(3x+5)=3x-1 | | a+2b=50 | | 5x=3/7 | | 5x^3=3x^2 | | 12+3p=2p+4 |

Equations solver categories